2014
DOI: 10.1186/1476-4598-13-215
|View full text |Cite
|
Sign up to set email alerts
|

The DEK oncoprotein binds to highly and ubiquitously expressed genes with a dual role in their transcriptional regulation

Abstract: BackgroundThe DEK gene is highly expressed in a wide range of cancer cells, and a recurrent translocation partner in acute myeloid leukemia. While DEK has been identified as one of the most abundant proteins in human chromatin, its function and binding properties are not fully understood.MethodsWe performed ChIP-seq analysis in the myeloid cell line U937 and coupled it with epigenetic and gene expression analysis to explore the genome-wide binding pattern of DEK and its role in gene regulation.ResultsWe show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…[43][44][45] The specific mechanism of action involves preferential binding to transcription start sites of highly transcribed genes in areas of hypomethylation. 46 In addition, recent studies have shown that DEK signaling promotes both the production and secretion of Wnt ligands to promote canonical β-catenin signaling. 36,47 The DEK fusion partner ARMC12 is an Armadillo (Arm) repeatcontaining protein, which is the homolog of Modern Pathology (2017) 30, 998-1012 mammalian β-catenin, and these have been implicated in canonical β-catenin signaling through the regulation of β-catenin stability and interaction with adherens junctions, as well.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] The specific mechanism of action involves preferential binding to transcription start sites of highly transcribed genes in areas of hypomethylation. 46 In addition, recent studies have shown that DEK signaling promotes both the production and secretion of Wnt ligands to promote canonical β-catenin signaling. 36,47 The DEK fusion partner ARMC12 is an Armadillo (Arm) repeatcontaining protein, which is the homolog of Modern Pathology (2017) 30, 998-1012 mammalian β-catenin, and these have been implicated in canonical β-catenin signaling through the regulation of β-catenin stability and interaction with adherens junctions, as well.…”
Section: Discussionmentioning
confidence: 99%
“…DEK is expressed in most human tissues (Sanden et al 2014) and plays a role in both transcriptional activation and gene transrepression (Campillos et al 2003, Sammons et al 2006). However, we are still in the infancy stage of understanding its defined role in gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Data were analyzed as described by Sanden et al 16 with some modifications and extensions as detailed in the Online Supplementary Methods.…”
Section: Discussionmentioning
confidence: 99%